Association Between Dietary Fiber Intake and Risk of Depression in Patients With or Without Type 2 Diabetes - Mao, Yafei; Li, Xinyuan; Zhu, Shumin; Geng, Yulan (Frontiers in Neuroscience, 2022)
(1) Background: Depression and type 2 diabetes (T2D) are both serious public health problems, with morbidity and mortality in people increasing year by year, resulting in a heavy economic burden. A correlation between dietary fiber and both has been reported. Nevertheless, few data are available concerning dietary fiber and the risk of depression with or without T2D, which deserve further attention; (2) Methods: We assessed the relationship between dietary fiber intake and risk of depression with or without T2D in the 2007-2014 National Health and Nutrition Examination Survey (NHANES) population. A 24-hour dietary review was used to assess fiber intake. The Patient Health Questionnaire-9 was used to assess depression. Stability of the results was assessed using restricted cubic spline models and logistic regression, as well as sensitivity analyses; (3) Results: A total of 17,866 adults aged 20 years and older with a mean age of 49.3±17.7 years were included in this study, of whom 49.5% were male. After adjusting for covariates, the association of dietary fiber intake with the risk of depression appeared to differ between non-T2D group and T2D group (OR, 0.987; 95% CI, 0.979-0.995 vs. OR, 1.003; 95% CI, 0.988-1.017). Furthermore, when dietary fiber was converted to a categorical variable, there was evidence of interaction between T2D status and fiber intake on decreasing the prevalence of depression (p-value for interaction=0.015). Sensitivity analysis showed stable results. (4) Conclusions: Our findings indicated that whether a patient has T2D may affect the relationship between dietary fiber intake and the risk of depression, which still needs to be confirmed by further randomized controlled trials.